Friction-Induced Vibration in Lead Screw Drives - Vahid-Araghi, Orang; Golnaraghi, Farid; SpringerLink (Online service). (New York, NY Springer New York Imprint: Springer, 2011)
Friction-Induced Vibration in Lead Screw Drives covers the dynamics of lead screw drives with an emphasis on the role of friction. Friction-induced vibration in lead screws can be the cause of unacceptably high levels of audible noise as well as loss of operation accuracy and shortened life. Although lead screw drives have a long history and their mechanical design and manufacturing aspects are very well understood, the role of friction in their dynamical behavior has not been comprehensively treated. The book draws on the vast body of work on the subject of dynamical systems with friction (such as disk brake systems) and offers said treatment, along with: · Unique coverage of modeling of multi-DOF lead screw systems with friction Detailed analysis of negative damping, mode coupling, and kinematic constraint instability mechanisms in lead screws drives ·A practical parameter identification approach for the velocity dependent coefficient of friction in lead screw drives Friction-Induced Vibration in Lead Screw Drives serves as the definitive text on the friction-induced vibration of lead screws, and includes a practical case study where the developed methods are used to study the excessive noise problem of a lead screw drive system and to put forward design modifications that eliminate the friction-induced vibrations.
Introduction -- Mathematical Modeling of Lead Screw Drives -- Negative Damping -- Kinematic Constraint -- Mode Coupling -- An Experimental Case Study -- Appendices.
Electronic reproduction.
Keywords: Screwdrivers--Vibration.; Self-induced vibration; Friction; Electronic books